Investigation of Hydroxymethylfurfural Formation in Herle. Issue 12 (1st December 2016) - Baltacı, Cemalettin; Ilyasoglu, Huri; Gundogdu, Ali; Ucuncu, Osman
Abstract : Mulberry pestil and köme are Turkish traditional foods made from herle. Browning leads to quality losses in the herle, and its products. In this study, the effect of thermal treatment on the hydroxymethylfurfural formation and color values in the herle was evaluated. The herle samples were kept at different temperatures (60–110°C) and times (2–6 h). The hydroxymethylfurfural formation was found to increase with increasing time and temperature. The legal limit for hydroxymethylfurfural in the pestil (50 mg/kg) was exceeded at temperatures above 90°C. The lightness ( L* value) of the sample decreased with the thermal treatment, indicating browning.